Epiphyte biodiversity in the coffee agricultural matrix canopy stratification and distance from forest fragments - Moorhead, Leigh C (Conservation biology : the journal of the Society for Conservation Biology, 2010)
Quality of the agricultural matrix profoundly affects biodiversity and dispersal in agricultural areas. Vegetatively complex coffee agroecosystems maintain species richness at larger distances from the forest. Epiphytes colonize canopy trees and provide resources for birds and insects and thus effects of agricultural production on epiphytes may affect other species. We compared diversity, composition, and vertical stratification of epiphytes in a forest fragment and in two coffee farms differing in management intensity in southern Mexico. We also examined spatial distribution of epiphytes with respect to the forest fragment to examine quality of the two agricultural matrix types for epiphyte conservation. We sampled vascular epiphytes in a forest fragment, a shade polyculture farm, and a shade monoculture farm at 100 m, 200 m, and 400 m from the forest. Epiphyte and orchid richness was greater in the forest than in the monoculture but richness was similar in the forest and polyculture farm. Epiphyte species composition differed with habitat type, but not with distance from the forest. In the forest, epiphytes were distributed throughout tree canopies, but in the farms, epiphytes were primarily found on trunks and larger branches. Epiphyte richness and species similarity to forest species declined with distance from the forest fragment in the monoculture, but richness and similarity to forest species did not decline with distance from forest in the polyculture. This suggests polyculture coffee has greater conservation value. In contrast, monoculture coffee is likely a sink habitat for epiphytes dispersing from forests into coffee. Coffee farms differ from forests in terms of the habitat they provide and species composition, thus protecting forest fragments is essential for epiphyte conservation. Nonetheless, in agricultural landscapes, vegetatively complex coffee farms may contribute to conservation of epiphytes more than other agricultural land uses